Memprediksi Intensi Membeli Ulang dan Word-of-Mouth Pengunjung Perhelatan Musik - Winarno, Ahmad Faizy; Firdaus, Ghafiki Keysha; Wibowo, A. J. Ibnu; Yudianto, Bernardinus Realino (Kajian Branding Indonesia, 2025)
This research aims to analyze the influence of music performance visitor involvement on value co-creation behavior, visitor experience, intention to repurchase music performance tickets, and word of mouth. The research method used is quantitative with a focus on the Jabodetabek area and informants who have musical knowledge. It is hoped that the results will contribute to academic understanding in the field of music branding and marketing as well as provide practical insight for the music industry. Research limitations include subjects who are fans of music performances in Indonesia.